KAJIAN FILOSOFIS-HISTORIS HUBUNGAN NEGARA DAN AGAMA - Armawi, Armaidy (Paramita: Historical Studies Journal, 2013)
The issue of the relation between state and religion as socio-politic phenomena in Indonesia has been up and down in the Indonesian history. Therefore, it can be said as a latent issue in the life of the nation and state. This study employs the theory of ideological-philosophical transformation of Pancasila as anthropological basis of the nature of mono-pluralist human beings. In order to discuss the issue in the historical-philosophical approach, analysis and synthesis methods together with verstehen, interpretation and hermeneutic methods are employed. The relation between state and religion has been finalized by the founding fathers. They tried not to fall into the trap of the dichotomy between secular and religious state. They creatively-innovatively developed the thought of the relation between state and religion, which is the Indonesian uniqueness; the State of Republic of Indonesia which believes in one God in accordance with the basis of just and civilized humanity. Key words: reflection, philosophical, relation, state and religionÃ‚Â Persoalan hubungan negara dan agama sebagai fenomena sosial politik di Indonesia menunjukkan adanya suatu kondisi pasang surut dalam perjalanan sejarah. Oleh karena itu, permasalahan ini dapat dikatakan bersifat latent dalam kehidupan berbangsa dan bernegara. Kajian ini menggunakan teori transformasi ideologi dan filsafat Pancasila sebagai dasar antroplogis hakikat manusia monopluralis. Dalam membahas persoalan tersebut digunakan pendekatan historis-filosofis melalui metode analisis dan sintesis serta dilengkapi pula dengan metode verstehen, interpretasi dan hermeunetika. Hubungan negara dan agama oleh pendiri Negara Republik Indonesia telah diselesaikan secara final. Pendiri negara berupaya untuk tidak terjebak dalam dikotomi negara sekular dan negara agama. Pendiri negara secara kreatif-inovatif membangun pemikiran hubungan negara dan agama yang khas Indonesia, yaitu negara ber-Ketuhanan Yang Maha Esa menurut dasar kemanusiaan yang adil dan beradab. Kata kunci: refleksi, filosofis, hubungan, negara dan agama